2016
DOI: 10.1016/j.asjsur.2015.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral idiopathic granulomatous mastitis

Abstract: Bilateral IGMs have a higher rate of more relapse and greater resistance to medical therapies than do unilateral IGMs. Surgical management should be avoided unless all medical treatment options have been exhausted. Nevertheless, expectant management seems a rational option for the treatment of bilateral IGM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 58 publications
1
53
0
1
Order By: Relevance
“…Patients with GM are typically women of childbearing age; a median age of approximately 35 years has been a relatively consistent finding. [2][3][4][5] Hormonal factors are hypothesised to contribute because of the association with parity, current pregnancy and the oral contraceptive pill. GM is rarely seen in nulliparous women, and the majority of patients are within five years of a pregnancy, supporting the theory of a hormonal aetiology.…”
Section: Aetiologymentioning
confidence: 99%
“…Patients with GM are typically women of childbearing age; a median age of approximately 35 years has been a relatively consistent finding. [2][3][4][5] Hormonal factors are hypothesised to contribute because of the association with parity, current pregnancy and the oral contraceptive pill. GM is rarely seen in nulliparous women, and the majority of patients are within five years of a pregnancy, supporting the theory of a hormonal aetiology.…”
Section: Aetiologymentioning
confidence: 99%
“…Velidedeoglu et al 13 reported a relatively large series, with 10 patients diagnosed with bilateral IGM. Others reported left or equal involvement 12 14…”
Section: Discussionmentioning
confidence: 99%
“…Velidedeoglu et al 13 found that patients with bilateral IGM have a higher rate of relapse and greater resistance to medical therapies than patients with unilateral IGM. In our study, five patients with IGM had bilateral involvement and four patients had recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Velidedeoglu et al . [23] also found that antituberculous treatment was effective in the treatment of a patient with bilateral disease. Recently, Farouk et al [24] reported that in their prospective study including 30 GLM patients, rifampicin (300 mg twice daily for 6-9 months) was an effective therapy.…”
Section: Discussionmentioning
confidence: 99%